PERBANDINGAN SIFAT FISIKAWI SELULOSA BAKTERI YANG DIPRODUKSI ISOLAT KRE-12 DENGAN METODE FERMENTASI STATIS DAN PENGGOJOGAN - Sarkono Sarkono; Sukarti Moeljopawiro; Bambang Setiaji; Langkah Sembiring (Universitas Sebelas Maret, 2014)
Abstract- Cellulose production in bacteria is influenced by the fermentation method, both quantitatively and qualitatively. Bacterial cellulose produced by different fermentation methods were compared based on the dry weight of the cellulose produced. While the physical properties compared using SEM and XRD technique. Production of cellulose in acetic acid bacteria strain KRE-12 with static fermentation method, shaking 50 rpm, shaking 100 rpm and shaking150 rpm was0,49; 0,12; 0,13 and 0,10 g/100 ml, respectively. The degree of crystallinity by XRD method in static fermentation method was 91 %, shaking fermentation 100 rpm was73 % and shaking fermentation150 rpm was72%. Static fermentation method produces bacterial cellulose in thesheets form, while shaking fermentation produces fragmented cellulose with predominantly spherical shape. The observation of the surface structure of bacterial cellulose by SEM showed that the static fermentation method generates woven densely of cellulose microfibrils. The change from a static method to shaking fermentation causes the surface structure changes. Some changes have been observed in which woven microfibrils become more loose and form a larger gap between the holecellulose woven microfibrils. Keywords : acetic acid bacteria , bacterial cellulose, static fermentation, shaking